Dance and Pythagorean Symbolism: A Case Study - Eleni Filippidou; Georgia Paraskevi Gerogianni (Randwick International of Social Science Journal, 2022)
The research field of this paper is the community of Limni, which is located on the island of Evia in Greece. Τhe aim of this research paper is to study the symbolic dimension of the Kamarachti dance from the Limni of the island of Evia in Greece. In particular, the paper attempts to highlight the symbolic characteristics of the dance under study, in order to determine the reason for its performance during the Easter period, throughout which many rituals related to the regeneration of nature are performed, that is this paper attempts to determine its function. Data was gathered through ethnographic method as this is applied to the study of dance, while its elaboration with the comparative method. The Kamarachti was recorded and analyzed using the Laban notation system and the morphological method. Finally, the symbolic function of Kamarachti was interpreted on the basis of the Pythagorean philosophical tradition. From the data analysis was found that the Kamarachti dance in the community of Limni on the island of Evia, on the basis of its symbolism, emerges as the protector of a magical process that aims at the rebirth of nature. This dance, with its magical and laxative properties and powers, avoids any demonic imposition, in order to ensure the euphoria of the earth.